Design and Construction of a Web-Based Teacher Payroll System at Iqro Islamic Vocational School - Violla Cantika; Dipa Dyah Puspita Arum; Jupron Jupron (STMIK Methodist Binjai, 2026)
SMK Islam Iqro Pasar Kemis stilll uses al manual systeml in the teacher attendance andl payroll process, causing the administrative process to be less effective, requiring a long time, and at risk of miscalculation and data loss. The attendance process is carried out using a signature on the attendance sheet, while salary calculations are carried out manually based on the monthly attendance recap. These problems encourage thel need tol develop al system thatl is able tol automate the attendance and payroll processes in an integrated manner. Thisl study aimsl to designl and buildl a lWeb-Basedl Teacher Payrolll System at SMK Islam Iqro equippedl with al barcode attendance lfeature. The systeml was developedl using thel Waterfall methodl which includesl the stagesl of needsl analysis, systeml design, limplementation, and ltesting. Thel technologies usedl in developing the systeml are PHPl as al programming llanguage, MySQLl as al database, andl HTML, CSS, and JavaScript as user interfaces. The system has two main actors, namely admin and teacher. Teachers can take attendance using a barcode scan on an identity card, while the admin can manage teacher data, attendance data, payroll processes, and reports. The system automatically recaps attendance and calculates salaries based on attendance data stored in thel database. Systeml testing wasl conducted usingl the Blackl Box Testingl method and demonstrated thatl all key system featuresl functioned accordingl to userl requirements. Thel results indicatel that thel system improved administrative process efficiency, minimized salary calculation errors, and facilitated real-time management of teacher attendance and payroll data.